Quantification and significance of extraprostatic findings on prostate MRI: a retrospective analysis and three-tier classification - Wagnerova, Monika; Macova, Iva; Hanus, Petr; Jurka, Martin; Capoun, Otakar; Lambert, Lukas; Burgetova, Andrea (Insights into imaging, 2023)
OBJECTIVES: To quantify extraprostatic findings (EPFs) on prostate MRI, estimate the proportion of reported and unreported EPFs, assess their clinical importance, and propose standardized reporting of EPFs. MATERIALS AND METHODS: Prostate 3-T MRI studies, reports, and clinical data from 623 patients (age 67.9 ± 8.2 years) were retrospectively analyzed and re-evaluated for the presence of EPFs and their clinical significance: E1-no finding or findings that have no clinical significance; E2-potentially significant findings; and E3-significant findings. RESULTS: Secondary reading identified 1236 EPFs in 593 patients (1.98 ± 1.13 EPFs per patient, no EPFs in 30 patients), from which 468 (37.8%) were mentioned in the original report. The most common findings included diverticulosis (44% of patients), hydrocele (34%), inguinal fat hernia (16%), and bladder wall trabecular hypertrophy (15%). There were 80 (6.5%) E2 EPFs and 30 (2.4%) E3 EPFs. From E3 EPFs, 10 (33%) were not originally reported. A workup was suggested in 35 (52%) of the 67 originally reported E2 and E3 findings with follow-up and performed in 20 (30%). Fourteen (21%) EPFs in 11 patients influenced their management. Four experienced radiologists originally reported 1.8 to 2.5 findings per patient (p < 0.0001). CONCLUSIONS: EPFs on prostate MRI are frequent, but only 2.4% are clinically significant (E3), and 33% of these are not reported. Only 30% of E2 and E3 findings are further explored, and 21% influence patient management. We suggest that an "E" category should be attached to the PI-RADS system to identify the presence of EPFs that require further workup. CRITICAL RELEVANCE STATEMENT: Extraprostatic findings on prostate MRI are frequent, but only 2.4% are clinically significant (E3), and 33% of these are not reported. We advocate standardized reporting of extraprostatic findings indicating their clinical significance. KEY POINTS: • Extraprostatic findings on prostate MRI are frequent with an average of two findings per patient. • 2.4% of extraprostatic findings are significant, and 33% of these are not reported. • There is a significant variability among experienced radiologists in reporting extraprostatic findings.